Finding the Fundamental: Shaping Identity in Gender and Sexual Orientation Based Asylum Claims - Hinger, Sarah (Columbia Journal of Gender and Law, 2010)
Within the United States and globally, gender and sexual orientation form the basis of an increasing number of rights claims and protections. Both grounds, which reflect the expanding notions and challenges of identity-based rights, have been incorporated into United States asylum law with varying success. The extension of asylum to include some claims based on gender and sexual orientation has real and immediate significance for many individuals. However, securing protection in an individual case sometimes creates precedents that make it more difficult to prevail in future asylum claims, and that limit conceptions of gender and sexual orientation within the broader movement for human rights. To obtain asylum in the United States, an applicant must be a member of a particular social group targeted for persecution on the basis of a characteristic so fundamental to identity that it cannot or should not be required to change.’ Applying this standard, adjudicators seek to understand what about gender or sexual orientation unites a group of people to the extent that it places members collectively at risk of persecution. Thus, the surest way for applicants and advocates to demonstrate that the asylum standard is met is to put forward a familiar and universalized picture of the persecuted woman, lesbian, or gay man, minimizing variability or complicating factors in the individual case. These firm but under-theorized depictions of gender and sexual orientation create and reinforce limited conceptions of identity and culture that make it more difficult to raise new asylum claims within these established categories. Existing asylum law should incorporate a more careful analysis of the harms that occur in these claims, particularly the successful ones, in order to find and permit a more robust view of identity and culture.